2017
DOI: 10.1111/1471-0307.12454
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Bacillus cereus biofilm removal in the dairy industry using an in vitro model of cleaning‐in‐place incorporating serine protease

Abstract: This article addresses a major hygienic issue in the dairy industry, namely biofilm removal. Response surface methodology was deployed to optimise Bacillus cereus biofilm removal conditions using serine protease. The currently practiced alkali cleaning‐in‐place (CIP) method was also optimised, and while the optimised protease CIP resulted in complete removal of biofilm cells, the reference CIP (with alkali) resulted in a reduction of 4.08 log biofilm cells/cm2 and the optimised alkali CIP resulted in a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Kumari and Sarkar [ 33 ] used a serine protease, resulting in a complete reduction in B. cereus biofilms (4.08 log 10 CFU/cm 2 ) developed in skim milk. The difference between this report and our results could be explained by the low cell density in the biofilms; moreover, after 24 h of incubation, the EPS matrix is not mature [ 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kumari and Sarkar [ 33 ] used a serine protease, resulting in a complete reduction in B. cereus biofilms (4.08 log 10 CFU/cm 2 ) developed in skim milk. The difference between this report and our results could be explained by the low cell density in the biofilms; moreover, after 24 h of incubation, the EPS matrix is not mature [ 19 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of different enzymes on the detachment of different microorganisms in biofilms has also been thoroughly studied. To this effect, Kumari and Sarkar (2018) observed that the use of a serine protease included in a cleaning-in-place (CIP) alkali resulted in a complete reduction of 4.08 log CFU cm −2 of Bacillus cereus biofilms. This greater increase in efficacy compared with the results of our study could be explained by the fact that the cell density of the biofilm generated in this study was not very high and, therefore, a consolidated mature matrix would not have been produced.…”
Section: Evaluation Of the Biofilm By The Culture Methodsmentioning
confidence: 99%
“…Protease is considered to be an effective method for EPS removal (Schallenberger et al 2012 ; Thallinger et al 2013 ). For example, serine proteases produced by S. epidermidis can eradicate pre-formed biofilms (Martínez-García et al 2018 ; Kumari and Sarkar 2018 ; Weldrick et al 2019 ). The eDNA with glue effect integrates bacteria and other components into a 3D framework, which is beneficial in helping to promote bacterial adhesion and gene transfer (Jakubovics et al 2013 ; Okshevsky and Meyer 2015 ; Fleming and Rumbaugh 2017 ).…”
Section: Dispersion Mechanisms Of Different Types Of Dispersantsmentioning
confidence: 99%